2020
DOI: 10.14569/ijacsa.2020.0110718
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Pre-Class Learning Content Approach for the Implementation of Flipped Classrooms

Abstract: The nascent recognition of computing in curriculum across countries is also accompanied by several pedagogic inefficiencies especially concerning insufficient time available for teacher-student interaction. In this paper, a flipped classroom concept was identified as an effective approach to teaching students at various levels in the academia including Higher Education. Preparing the pre-class content and considering the format used to deliver it has not gained much consideration. There are several ways in whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The previous research studies [8,9,61] showed the different approaches for student engagement measurement. According to previous studies, the different approaches are face features, eyeball tracking, eye gaze, body gestures, head motions, body surface temperature, mouse movements, and keystrokes.…”
Section: Related Workmentioning
confidence: 99%
“…The previous research studies [8,9,61] showed the different approaches for student engagement measurement. According to previous studies, the different approaches are face features, eyeball tracking, eye gaze, body gestures, head motions, body surface temperature, mouse movements, and keystrokes.…”
Section: Related Workmentioning
confidence: 99%
“…Previous investigations [24][25][26] have examined diverse methodologies aimed at assessing student engagement, which include analyzing facial characteristics, monitoring eyeball movements, evaluating eye gaze patterns, interpreting bodily gestures, tracking head movements, measuring body surface temperature, analyzing mouse behaviors, and observing keystrokes. Typically, these studies entailed scrutinizing stored videos and images of students within traditional classroom environments.…”
Section: Research Of Facial Expression Recognition and Learning Emoti...mentioning
confidence: 99%